Effects of Probiotic (Bacillus subtilis) Supplementation During Offseason Resistance Training in Female Division I Athletes. Issue 11 (November 2020) - Toohey, Jeremy C.; Townsend, Jeremy R.; Johnson, Sean B.; Toy, Ann M.; Vantrease, William C.; Bender, David; Crimi, Chelsea C.; Stowers, Kathryn L.; Ruiz, Matthew D.; VanDusseldorp, Trisha A.; Feito, Yuri; Mangine, Gerald T.
Abstract : Abstract: Toohey, JC, Townsend, JR, Johnson, SB, Toy, AM, Vantrease, WC, Bender, D, Crimi, CC, Stowers, KL, Ruiz, MD, VanDusseldorp, TA, Feito, Y, and Mangine, GT. Effects of probiotic ( Bacillus subtilis ) supplementation during offseason resistance training in female Division I athletes. J Strength Cond Res 34(11): 3173–3181, 2020–We examined the effects of probiotic ( Bacillus subtilis ) supplementation during offseason training in collegiate athletes. Twenty-three Division I female athletes (19.6 ± 1.0 years, 67.5 ± 7.4 kg, and 170.6 ± 6.8 cm) participated in this study and were randomized into either a probiotic ( n = 11; DE111) or placebo ( n = 12; PL) group while counterbalancing groups for sport. Athletes completed a 10-week resistance training program during the offseason, which consisted of 3–4 workouts per week of upper- and lower-body exercises and sport-specific training. Athletes consumed DE111 (DE111; 5 billion CFU/day) or PL supplement daily for the entire 10-week program. Before and after training, all athletes underwent 1 repetition maximum (1RM) strength testing (squat, deadlift, and bench press), performance testing (vertical jump and pro-agility), and isometric midthigh pull testing. Body composition (body fat [BF]%) was completed using BODPOD and bioelectrical impedance analysis, as well as muscle thickness (MT) measurement of the rectus femoris (RF) and vastus lateralis using ultrasonography. Separate repeated-measures analyses of variance were used to analyze all data. Significant ( p ⩽ 0.05) main effects for time were observed for improved squat 1RM, deadlift 1RM, bench press 1RM, vertical jump, RF MT, and BF%. Of these, a significant group × time interaction was noted for BF% ( p = 0.015), where greater reductions were observed in DE111 (−2.05 ± 1.38%) compared with PL (−0.2 ± 1.6%). No other group differences were observed. These data suggest that probiotic consumption in conjunction with post-workout nutrition had no effect on physical performance but may improve body composition in female Division I soccer and volleyball players after offseason training.